Integrating 3D technology with the Sampaio classification for enhanced percutaneous nephrolithotomy in complex renal calculi treatment - Zhang, Jiamo; Qing, Jing; Hu, Ke; Cheng, Honglin (Frontiers in Surgery, 2024)
BackgroundTo investigate the safety and efficacy of percutaneous nephrolithotomy (PCNL) in the treatment of complicated renal calculi by integrating three-dimensional (3D) computed tomography (CT) reconstruction with the Sampaio classification of the renal collecting system.MethodsSixty-four consecutive patients with complex kidney calculi who underwent PCNL between January 2019 and October 2023 were retrospectively analyzed and divided into experimental group (3D printing) and control group (CT imaging) according to their willingness to pay for 3D imaging. Both groups underwent preoperative CT urography. The Digital Imaging and Communications (DICOM) in Medicine data of the experimental group from CT imaging were used for 3D reconstruction and model printing. Then, the Sampaio classification system was used to design the puncture channel and develop a surgical strategy.ResultsThe 3D-printed models of the experimental group successfully displayed the Sampaio classification system. There was no significant difference in the baseline parameters between the groups. Compared with the control group, the experimental group exhibited significant improvements in the puncture time, number of puncture needles, number of puncture channels, target calyx consistency, number of first puncture channels, and stone clearance. There were no significant differences in the total operative time, decrease in the hemoglobin level, length of hospital stay, and postoperative complications between the groups.ConclusionsIntegration of 3D technology with the Sampaio classification of the renal collecting system can enhance the preoperative evaluation and planning of percutaneous renal access. This approach allows a more precise method of PCNL for treating complex renal calculi.